Changing methods and methods of change: reflections on qualitative research in Sport for Development and Peace. Issue 5 (19th October 2016) - Darnell, Simon C.; Whitley, Meredith A.; Massey, William V.
Abstract: This collection of papers is made up of diverse, contemporary, and thought-provoking examples of qualitative methods in the study of Sport for Development and Peace (SDP). In this conclusion, we reflect on some of the key themes that cut across the contributions. Four main topics are discussed: Interpretation (the subjects and voices at the centre of SDP research), Outcomes (the variety of results that are likely to emerge from SDP research), Creativity and Diversity (the need for SDP research that is novel, nuanced, and sometimes messy), and Hope (the productive tension between critique and optimism in SDP research). Through this deliberation, we advocate for an ongoing and even renewed commitment to the qualitative study of SDP, one that moves beyond the rather strict confines of Monitoring & Evaluation and towards an embrace of the full range of social and political implications that emerge from the activities of SDP.